Effects of straw and plastic film mulching on microbial functional genes involved in soil nitrogen cycling - Dou, Ying; Wen, Mengmeng; Yang, Caidi; Zhao, Fazhu; Ren, Chengjie; Zhang, Nannan; Liang, Yinyan; Wang, Jun (Frontiers in Microbiology, 2023)
Microorganisms regulate soil nitrogen (N) cycling in cropping systems. However, how soil microbial functional genes involved in soil N cycling respond to mulching practices is not well known. We collected soil samples from a spring maize field mulched with crop straw (SM) and plastic film (FM) for 10-yr and with no mulching (CK) in the Loess Plateau. Microbial functional genes involved in soil N cycling were quantified using metagenomic sequencing. Compared to that in CK, the total abundance of genes involved in soil N cycling increased in SM but had no significant changes in FM. Specifically, SM increased the abundances of functional genes that involved in dissimilatory nitrate reduction to ammonium (nirB, napA, and nrfA), while FM decreased the abundances of functional genes that involved in ammonification (ureC and ureA) in comparison with CK. Other genes involved in assimilatory nitrate reduction, denitrification, and ammonia assimilation, however, were not significantly changed with mulching practices. The nirB and napA were derived from Proteobacteria (mainly Sorangium), and the ureC was derived from Actinobacteria (mainly Streptomyces). Mental test showed that the abundance of functional genes that involved in dissimilatory nitrate reduction was positively correlated with the contents of soil microbial biomass N, potential N mineralization, particulate organic N, and C fractions, while ammonification related gene abundance was positively correlated with soil pH, microbial biomass C and N, and mineral N contents. Overall, this study showed that SM could improve soil N availability and promote the soil N cycling by increasing the abundance of functional genes that involved in DNRA, while FM reduced the abundance of functional genes that involved in ammonification and inhibited soil N cycling.